The Impact of Strategic Performance Index and Intellectual Capital on Sharia Commercial Banks in Indonesia - SUPRIYANTO, JUNI; MURWANINGSARI, ETTY (Journal of Ecohumanism, 2024)
The purpose of this study is to determine how the Islamic Performance Index and Intellectual Capital affect Indonesia’s Sharia Commercial Banks’ financial performance from 2013 to 2023. Every year, the banking industry grows, making sharia banking necessary to rival traditional banking. Sharia banks must be able to increase their profitability by focusing on added value via intelligence and sharia compliance because conventional banking still commands a larger portion of the market and more consumers than sharia banks. In this investigation, panel data regression is used in conjunction with the WarpPLS 8.0 program to create the Structural Equation Model Partial Least Square (SEM-PLS). The results of this study show that the VAIC has a fairly favorable impact on the performance of the VAIC Sharia Commercial Bank. ROA is unaffected by VAHU or VACA, however there is a significant positive benefit from the three markers used to measure IC VACA. ZPR has no influence on ROA, but PSR and IsIN have an impact on ROA for IPI.